Clinical and imaging findings in enteropathic spondyloarthritis with special emphasize in diagnostic delay: a cross-sectional study - Paola Conigliaro; Arianna D'Antonio; Andrea Wlderk; Federico Sabuzi; Mario Ferraioli; Leonardo Sichi; Valerio Da Ros; Livia Biancone; Alberto Bergamini; Maria Sole Chimenti (SAGE Publishing, 2024)
Background: Enteropathic spondyloarthritides (eSpAs) are chronic inflammatory joint diseases associated with inflammatory bowel disease (IBD). Limited data are available on the prevalence since arthritis in IBD patients may be underestimated because medications may hide disease activity with a possible diagnostic delay. Objectives: We aimed to evaluate diagnostic delay in eSpA and explore associated demographic, clinical, and radiographic characteristics. Design: Single-centre cross-sectional study conducted on consecutive out-patients referred to the combined Gi-Rhe clinic (November 2018-October 2019). Methods: We analysed eSpA patients for diagnostic delay, disease activity, inflammatory markers, conventional radiography (CR) and magnetic resonance images (MRI) of sacroiliac joints/spine. Results: A total of 190 eSpA patients [118 peripheral SpA, 72 axial (Ax) SpA including 44 non-radiographic (nr)-axSpA] were enrolled. axSpA patients had a higher prevalence of men sex, HLA-B27 positivity, uveitis and pancolitis compared with peripheral eSpA. Median diagnostic delay in eSpA was 48 months (IQR 6-77) with no difference between axial and peripheral patients. Radiographic-axial SpA (r-axSpA) patients displayed a higher diagnostic delay compared with nr-axSpA (median/IQR 36/17-129 versus 31/10-57 months, p  = 0.03) and were older, with longer disease duration, low education status and high rate of employment than patients with nr-axSpA. r-axSpA patients with sclerosis, syndesmophytes and bridge at CR had higher diagnostic delay than those without lesions. Men showed higher prevalence of spine damage lesions than women as sclerosis, squaring, syndesmophytes and bridges. Longer disease duration was detected in patients with radiographic damage as bridge and sacroiliitis grade 3. On MRI, sacroiliac bone oedema was associated with reduced diagnostic delay, whereas bone erosions were associated with higher diagnostic delay compared with that in patients without these lesions. Patients with psoriasis displayed a higher diagnostic delay compared to those without skin involvement. Conclusion: Diagnostic delay was higher in r-axSpA compared with nr-axSpA despite the same treatment. Demographic, clinical features and radiological lesions were associated with diagnostic delay.